Structural changes and ferroelectric properties of BiFeO3 - PbTiO3 thin films grown via a chemical multilayer deposition method - Gupta S.; Garg A.; Agrawal D.C.; Bhattacharjee S.; Pandey D. (My University, 2025)
Thin films of (1-x) BiFeO3 -x PbTiO3 (BF-xPT) with x≈0.60 were fabricated on Pt/Si substrates by chemical solution deposition of precursor BF and PT layers alternately in three different multilayer configurations. These multilayer deposited precursor films upon annealing at 700 °C in nitrogen show pure perovskite phase formation. In contrast with the equilibrium tetragonal structure for the overall molar composition of BF:PT